Fixing to die: Kazuo Ishiguro's reinvention of the Bildungsroman. Issue 12 (1st December 2020) - Ng, Lynda
ABSTRACT: The Bildungsroman could be described as a 'future-facing' genre, in that its protagonist is exposed to the vicissitudes of life, gains experience, and comes of age; he or she, in other words, learns how to live. The horizon of such stories, beyond just the events being depicted, is the individual's life to come. In this paper, by contrast, I argue that a significant part of the coming-of-age process is the subject's confrontation with mortality. This kind of encounter is crucial to Martin Heidegger's philosophy, wherein he suggests that an authentic self can only be discovered via a confrontation with one's own finitude. In similar fashion, to leave one's childhood behind, in the classic Bildungsroman denouement, can be seen in this Heideggerian light as a coming to terms with the end of life. This complex interplay between maturity and mortality is starkly evident in Kazuo Ishiguro's 2005 novel, Never Let Me Go . Whilst it is frequently read as science fiction because of its concern with the ethics of cloning and organ harvesting, I consider it instead as an inverted Bildungsroman . Rather than a passage to adulthood and future life, the protagonist must come to terms with certain death; rather than learning how to live, she (and her fellow clones) must instead learn how to die. This essay shows how Ishiguro attests to the continued pertinence of the Bildungsroman form, even as he seeks to update it in the face of technological change.